Value Pluralism and Islamic Moral Education: A Philosophical Reconstruction of Akhlak Education in Plural Societies - Agus Khumaedy; Ahmad Ta’rifin; Hani Hasnah Safitri; Ulul Albab; Mohammad Adam (Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
This article examines the reconstruction of Islamic moral education through the integration of value pluralism within the framework of Islamic educational philosophy. The study addresses the challenge of moral complexity and value conflicts in contemporary pluralistic Muslim societies. The research aims to formulate a conceptual model of moral education that remains normatively grounded in Islamic values while being responsive to value diversity. Using a qualitative library research design, the study applies philosophical–normative analysis to key works in moral philosophy and Islamic educational thought, particularly the concepts of tawḥīd and maqāṣid al-sharī‘ah. The findings indicate that value pluralism can serve as a reflective ethical framework that acknowledges the diversity and incommensurability of values without leading to moral relativism. When dialogically integrated with Islamic normative principles, it produces a conceptual model of Islamic moral education that is adaptive, dialogical, and normatively oriented, fostering students’ capacity for moral deliberation and ethical responsibility in pluralistic societies.